2014
DOI: 10.1002/jrs.4471
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy and X‐ray diffraction applied to the study of Cretaceous fish fossils from Araripe Basin, Northeast of Brazil

Abstract: In this work, we investigate fossils of the fish coelacanth belonging to the Cretaceous Period from two different formations belonging to Araripe Basin (Brejo Santo and Romualdo Formations), in Northeast of Brazil, through Raman and infrared spectroscopy and X‐ray diffraction. The coelacanth processes of fossilization have occurred of different manners as a consequence of the different environment surrounding the fossils. The results obtained by different techniques showed that the matrix found in the Romualdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
10
0
3
Order By: Relevance
“…Specifically, the bands centered at 467 and 557 cm −1 are associated with antisymmetric deformation of PO 3− 4 ion, while the bands around 1020 cm −1 are related to the antisymmetric stretching of PO 3− 4 . Furthermore, calcite bands at 875 cm −1 correspond to symmetric deformations of CO 2− 3 , and bands at 1419 and 1460 cm −1 due to symmetric stretchings of CO 2− 3 were observed [2][3][4]. IR results were synergistic with the XRF and XRD analysis, suggesting together the presences of crystalline calcium, carbonate, and phosphate phases.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Specifically, the bands centered at 467 and 557 cm −1 are associated with antisymmetric deformation of PO 3− 4 ion, while the bands around 1020 cm −1 are related to the antisymmetric stretching of PO 3− 4 . Furthermore, calcite bands at 875 cm −1 correspond to symmetric deformations of CO 2− 3 , and bands at 1419 and 1460 cm −1 due to symmetric stretchings of CO 2− 3 were observed [2][3][4]. IR results were synergistic with the XRF and XRD analysis, suggesting together the presences of crystalline calcium, carbonate, and phosphate phases.…”
Section: Resultsmentioning
confidence: 82%
“…e IR spectra ( Figures 5 and 6) showed characteristic bands of hydroxyapatite [2][3][4]. Specifically, the bands centered at 467 and 557 cm −1 are associated with antisymmetric deformation of PO 3− 4 ion, while the bands around 1020 cm −1 are related to the antisymmetric stretching of PO 3− 4 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Freire and co‐workers used IR and Raman spectroscopy and XRD to the study of Cretaceous fish fossils from Araripe Basin of Northeast of Brazil. The results obtained by these techniques showed that the matrix found in the Romualdo Formation is composed of calcite and quartz, whereas the matrix found in the Brejo Santo Formation is comprised of calcite, quartz and albite . Jersek and Kamar used Raman microspectroscopy to identify gemstones from a chalice made in 1732 containing 456 embedded gemstones, one of the most richly decorated chalices in Slovenia.…”
Section: Art and Archeologymentioning
confidence: 99%
“…Coelacanth fossils from the Romualdo and Brejo Santo Geological formations in Brazil were studied by Freire et al . By utilisation of Raman, IR and XRD measurements, it was found that the coelacanth processes of fossilisation occurred in different manners depending on the environmental conditions the fossils were exposed to.…”
Section: Raman Spectroscopy In Paleontology and Prehistoric Artmentioning
confidence: 99%